The molecular mechanism of hPPARα activation. Issue 28 (20th March 2017) - Tang, Bowen; Li, Boqun; Qian, Yuqin; Ao, Mingtao; Guo, Kaiqiang; Fang, Meijuan; Wu, Zhen
Abstract : MD simulations were performed to explore the molecular mechanism of hPPARα activation. 11 key residues favouring binding ligands and the movements of helices and loops playing important roles in inducing the active conformation change of hPPARα were discovered. Abstract : Human peroxisome proliferator-activated receptor alpha (hPPARα) is a ligand-dependent transcription factor that mainly controls lipid metabolism in the liver. It has drawn wide attention as a significant target for developing new hypoglycaemic drugs. However, a central and largely unresolved question in finding new drugs targeted on hPPARα concerns ligand action mechanism: what makes certain molecules act as antagonists while others behave as agonists in the same binding site? To understand this, we performed a total of 600 ns all-atom molecular dynamics (MD) simulations to explore how four small molecule ligands bind to the hPPARα and play opposite effects. We characterized and compared the protein backbone fluctuation, and investigated the interaction networks and the movements of helixes and loops near binding site during MD simulations. Moreover, by free energy calculation and phylogenetic tree analysis, 11 key residues favouring binding ligands and some other residues playing important roles in inducing the active conformation changing of hPPARα were discovered. The results could help to understand the activation/deactivation of hPPARα by agonists or antagonists, and provide insightful prospective into hPPARα targeted structure-based drug designs.